A TEXTBOOK FOR THE LEFT? PROVIDING A FRAMEWORK FOR LEFT-WING EDUCATION POLICIES IN LATIN AMERICA - Burton, Guy (Revista Enfoques Educacionales, 2017)
The article presents a framework by which the approaches taken in educational policies by the Left in Latin America may be understood. This framework takes the form of a continuum by which left-wing or progressive education, between deep and shallow poles, drawing at an abstract level the continuum on the equalitydifference features associated with Bobbio’s (1996) Left-Right political spectrum. Presenting the Cuban (and to a lesser extent) the Sandinista Revolutions as the main source of progressive education in the region prior to the 1980s, the article examines the neo-liberal and neo-conservative features associated with the New Right and the Left’s response. This took several forms in the 1990s and 2000s: traditional communists (Cuba), Third Way reformers (e.g. the PSDB in Brazil and the Concertacion in Chile) and between first generation (e.g. PT, Frente Amplio, Izquierda Unida, Causa R, Sandinistas since 2007) and second generation (e.g. the Chavez, Morales and Correa governments) radicals. The educational approaches of each are then placed tentatively along the progressive education spectrum.